Political Representation in France and Germany
XIV, 350 p. 31 illus.
Keywords: Notwithstanding its contemporary critics, political representation remains at the core of democratic politics. Based on a comparative research project that gathered data from observations, surveys, experiments and expert interviews, this book examines the process and the quality of political representation in France and Germany from a dual perspective. First, it analyzes MPs’ behavior during their district activities. Second, it investigates the perceptions and evaluations of the represented, the French and German citizens. In ten chapters different facets of MPs’ activities as well as citizens’ attitudes are comparatively investigated. The book is relevant for Politics scholars and practitioners at national parliaments to better understand representative democracies, and it may also contribute to improve representation itself.